111k views
0 votes
3x - 4 = 2x 5

Which could be the first step in solving the equation represented by the model below?

3x - 4 = 2x 5 Which could be the first step in solving the equation represented by-example-1
User Tomblue
by
4.7k points

1 Answer

1 vote

The first step would be to gather all like terms onto the same side of the "=".

so,

the "-4" needs to be on the right and would become "+4".

the "2x" would need to be on the left side and would become "-2×"

the new equation would be:

3x-2x = 5+4

in turn, the solution would be:

x = 9

User Tamas Ionut
by
4.8k points